The Protection of Consumers’ Data whose Financing Application Rejected by Financial Service Institutions - Suwinto Johan; Amad Sudiro; Rayhan Mohmad Athallah Hafiz S. (Kertha Wicaksana, 2023)
Financial service institutions require financial service applicants’ data for financial capability evaluation. The data may include financial information, personal details such as property ownership, tax records, and family data. The submission of the data does not guarantee approval as some applications can be rejected. This study explored the the protection of customers’ data when their applications were denied. This normative juridical study regarded secondary data and library resources. The findings of this study highlighted the need for regulatory guidelines to protect customer data, particularly for those whose applications were rejected since their data could be misused by outsourced marketing personnel considering the absence of specific monitoring system. Even more, financial service institutions are not held accountable for such actions that occurred outside their scope of authority. In conclusion, regulatory measures must be established to protect and prevent unauthorized use of customers’ data.